PEMBELAJARAN FISIKA MELALUI INKUIRI TERBIMBING DENGAN METODE EKSPERIMEN DAN DEMONSTRASI DITINJAU DARI AKTIVITAS DAN PERHATIAN MAHASISWA1) - Jeffry Handhika (Jurnal Penelitian Pembelajaran Fisika, 2010)
The objective of the research are to know : (1) the effect of guided inquiryphysics learning using eksperiment and demonstration method to theconcept?óÔé¼Ôäós mastery in dynamic electricity, (2) the effect of high, medium andlow activity in physics learning to the concept?óÔé¼Ôäós mastery in dynamicelectricity, (3) the effect of high, medium and low physics learning collagestudent attention in physics learning to the concept?óÔé¼Ôäós mastery in dynamicelectricity, (4) interaction in physics learning between learning method andactivity to the concept?óÔé¼Ôäós mastery in dynamic electricity, (5) interaction inphysics learning between learning method and physics learning collegestudent attention to the concept?óÔé¼Ôäós mastery in dynamic electricity; (6)interaction in physics learning between activity and physics learning collagestudent attention to the concept?óÔé¼Ôäós mastery in dynamic electricity, (7)interaction in physics learning between learning method, activity and physicslearning collage student attention to the concept?óÔé¼Ôäós mastery in dynamicelectricity. The research is using experiment method. The technique ofanalyzing data is ANAVA three ways different cell. Based on the result of theresearch are concluded : (1) there is an effect of guided inquiry physicslearning using eksperiment and demonstration method to the concept?óÔé¼Ôäósmastery in dynamic electricity, (2) there is an effect of high, medium and lowactivity in physics learning to the concept?óÔé¼Ôäós mastery in dynamic electricity,(3) there is an effect of high, medium and low physics learning collagestudent attention in physics learning to the concept?óÔé¼Ôäós mastery in dynamicelectricity, (4) there is no interaction in physics learning between learningmethod and activity to the concept?óÔé¼Ôäós mastery in dynamic electricity, (5) thereis no interaction in physics learning between learning method and physicslearning second collage student attention to the concept?óÔé¼Ôäós mastery indynamic electricity; (6) there is no interaction in physics learning betweenactivity and physics learning collage student attention to the concept?óÔé¼Ôäósmastery in dynamic electricity, (7) there is no interaction in physics learningbetween learning method, activity and physics learning collage studentattention to the concept?óÔé¼Ôäós mastery in dynamic electricity.